IMPROVING THE EFFICIENCY OF RAILWAY TRACK MAINTENANCE ENTERPRISES (American Journal of Technology and Applied Sciences, 2025)
Railway infrastructure plays a critical role in ensuring the sustainability and competitiveness of transport systems. However, the efficiency of track maintenance enterprises remains a key challenge due to rising operational costs, technological requirements, and the need for safety. This study explores methods for enhancing the efficiency of railway track maintenance enterprises through organizational, technological, and economic measures. The findings suggest that digital monitoring systems, preventive maintenance strategies, and optimized resource allocation significantly improve performance indicators, reduce downtime, and increase cost-effectiveness.